2020
DOI: 10.3390/nano10020230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-Montmorillonite on Osteoblast Differentiation, Mineral Density, and Osteoclast Differentiation in Bone Formation

Abstract: Calcium-type montmorillonite, a phyllosilicate mineral, has diverse health benefits when introduced into the gastrointestinal tract or applied to the skin. However, the predominant use of this layered material has thus far been in traditional industries, despite its potential application in the pharmaceutical industry. We investigated the effects and mechanism of nano-montmorillonite (NM) on osteoblast and osteoclast differentiation in vivo and in vitro. We examined the osteogenic effects of NM with high calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Besides, the amount of CAK protein in CMS/GO/SF was remarkably lower than in CMS/SF group. These results should be assumed as Ca 2+ , Mg 2+ , and Si 4+ released from CMS resulted in the inhibition of osteoclastogenesis, which was identical to previously reported results [43,45]. It has been proved that magnesium deficiency could increase the generation of osteoclasts [46].…”
Section: In Vitro Osteoclastogenesis Of Cms/go/sf Scaffoldssupporting
confidence: 90%
“…Besides, the amount of CAK protein in CMS/GO/SF was remarkably lower than in CMS/SF group. These results should be assumed as Ca 2+ , Mg 2+ , and Si 4+ released from CMS resulted in the inhibition of osteoclastogenesis, which was identical to previously reported results [43,45]. It has been proved that magnesium deficiency could increase the generation of osteoclasts [46].…”
Section: In Vitro Osteoclastogenesis Of Cms/go/sf Scaffoldssupporting
confidence: 90%
“…Kundu et al [129] found that the addition of MMT significantly increased the alkaline phosphatase (ALP) expression of mesenchymal stem cells (MSCs). Kim et al [130] studied the effect and mechanism of nano-MMT on the differentiation of osteoblasts and osteoclasts in vivo and in vitro. On the one hand, nano-MMT improves the activity of ALP and the expression of related genes in osteoblasts, thereby stimulates the proliferation and differentiation of osteoblasts.…”
Section: Cation Exchange Modificationmentioning
confidence: 99%
“…Various preparation methods allow for the construction of different forms of antiosteoporotic CBNMs. The preparation methods discussed here include coprecipitation, ,,, ,,, sol–gel, , ,, , hydrothermal, ,,, electrochemical deposition, ,, electrostatic spray deposition, vapor diffusion, sonochemical synthesis, and physical crushing. Each preparation method has unique advantages and is accordingly suitable for the preparation of specific forms of CBNMs. The physicochemical properties of CBNMs prepared by different methods are summarized in Table .…”
Section: Cbnms For Osteoporosis Treatmentmentioning
confidence: 99%
“…Another unique application of CBNMs is in calcium supplements, a basic nutritional supplement for the nonpharmacological management of osteoporosis. , Calcium supplements often need to be taken in high daily doses, so the choice of calcium source is very important. , Osteoclast activation is usually associated with phosphate radicals, resulting in the formation of a local acidic microenvironment at bone resorption lacunae. CaC is therefore commonly chosen as a calcium supplement to avoid excessive phosphate intake. , Furthermore, nanotechnology can be used to improve the oral bioavailability of minerals due to the increase in dissolution rate as the particle size decreases .…”
Section: Cbnms For Osteoporosis Treatmentmentioning
confidence: 99%